The Effect of Attractions, Amenities, Accessibility on Tourist Satisfaction at Garuda Wisnu Kencana Bali - Octaviani, Lenny Kurnia; Kesuma, Wahyu Puja (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2024)
Garuda Wisnu Kencana (GWK) Bali is one of the most popular tourist destinations in Indonesia. The beauty of the Garuda Wisnu Kencana statue and the various attractions it offers attract many tourists to visit. This research aims to analyze the influence of attractions, facilities, and accessibility on tourist satisfaction at GWK Bali. This research uses quantitative methods and data collection techniques through surveys of 100 tourists who visited GWK Bali. Data were analyzed using validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, and F tests. The research results showed that attractions and accessibility had a positive and significant influence on tourist satisfaction at GWK Bali. On the other hand, facilities do not have a significant influence on tourist satisfaction. The coefficient of determination of 0.776 indicates that 77.6% of the variation in tourist satisfaction can be explained by a combination of attractions, facilities, and accessibility. Attractions and accessibility are important factors that influence tourist satisfaction at GWK Bali. GWK Bali management needs to improve the quality of attractions and accessibility to increase tourist satisfaction.